2004
DOI: 10.1144/gsl.sp.2004.232.01.12
|View full text |Cite
|
Sign up to set email alerts
|

Rapid quantitative mineral and phase analysis using automated scanning electron microscopy (QemSCAN); potential applications in forensic geoscience

Abstract: QemSCAN is a scanning electron microscope (SEM) system, initially designed to support the mining industry by providing rapid automated quantitative mineral analyses. The system is based upon Carl Zeiss SEMs fitted with up to four light-element energy dispersive X-ray spectrometers. Representative subsamples are mounted into either resin or wax blocks and polished prior to analysis, or can be mounted onto carbon tape. During analysis, X-ray spectra are collected at a user-defined pixel spacing and are acquired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
108
0
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(112 citation statements)
references
References 23 publications
0
108
0
4
Order By: Relevance
“…Perhaps in such circumstances it would be better not to use elemental chemical analyses at all (given the inherent problems that such techniques pose, as outlined above). If geochemical analyses were required, perhaps XRF analysis (which has been recognised as having greater accuracy [9]) or XRD analysis, that is able to provide mineralogical data from small samples [11], or indeed QemSCAN analysis [12] would be more appropriate.…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps in such circumstances it would be better not to use elemental chemical analyses at all (given the inherent problems that such techniques pose, as outlined above). If geochemical analyses were required, perhaps XRF analysis (which has been recognised as having greater accuracy [9]) or XRD analysis, that is able to provide mineralogical data from small samples [11], or indeed QemSCAN analysis [12] would be more appropriate.…”
Section: Introductionmentioning
confidence: 99%
“…The system is based upon a Zeiss E340 scanning electron microscope with four energy dispersive x-ray spectrometers (EDS). The resulting x-ray and backscattered electron signals (BSE) are compared with a database of known minerals and amorphous phases to produce a mineralogical identification [10][11][12]. Species with similar EDS-spectrum such as magnetite and hematite, can be differentiated by different BSE signal, while it is still difficult to separate magnetite and wüstite, since the software does not differentiate crystal structures [13].…”
Section: Methodsmentioning
confidence: 99%
“…Each spectrum is allocated to a specific mineralogy and sample mineralogy is inferred from the chemical spectra acquired and false colour images allow the visual comparison of samples (van Veen et al, 2013a(van Veen et al, , 2013b. A review of the QEMSCAN® applications is given by Pirrie et al (2009) and further details can be found in Gottlieb et al (2000); Pirrie et al (2004) and Pirrie and Rollinson (2011).…”
Section: Mineralogical and Microstructural Analysis By Automated Minementioning
confidence: 99%